Analisis Kemampuan Siswa dalam Menyelesaikan Soal Matematika Menggunakan Pendekatan Saintifik Berdasarkan Tahapan Heuristik Polya - Reski Awalia Ramadani; Anetha L. F. Tilaar; Santje M. Salajang (Departement of Mathematics Education, 2024)
In accordance with the problem formulation, namely the evaluation carried out by students when solving mathematics problems and the aim is to see how effective the application of the scientific approach with the Polya Heuristic stages is to problems. Solving mathematics problems for students uses descriptive qualitative research based on research findings in classes VIIA and VIIB of SMP Negeri 2 Tompaso about analyzing students' ability to answer mathematics questions using a scientific approach with polya heuristic steps. In general, it shows the existence of factors or obstacles that influence class VII students at SMP Negeri 2 Tompaso when working on mathematics questions given by their teacher. This is shown by children's complaints about mathematics subjects which they say are very difficult and cannot be understood well so that they have no interest or interest in mathematics subjects and as a result they are unable to do the mathematics problems given during observations at school. and taking part in the teaching process for almost a month, it can be seen that students at SMP Negeri 2 Tompaso are more interested in other subjects than mathematics because their interest is lacking, and there are still students who cannot read and dictate questions so that is also a mistake. one of their obstacles in working on math problems. Their abilities can also be analyzed using the benchmark questions that have been given, they may almost be able to solve easy questions but not quite long story questions because they prefer to make up or look at the answers from their classmates for the reason that they are too lazy to read the good questions. long. So it can also be concluded that many students at SMP Negeri 2 who are in class VII A and B. Tompaso lack literacy due to a lack of interest in reading questions or introductory books that have been facilitated by the school, so this could be an obstacle for them in solving questions because of their lack of interest in literacy.